2, 4‐DINITROPHENOL PARTIALLY ALLEVIATES FERROCYANIDE‐INDUCED TOXICITY IN Drosophila melanogaster. Issue 3 (7th October 2013) - Lozinsky, Oleksandr V.; Lushchak, Oleh V.; Lushchak, Volodymyr I.
<x xml:space="preserve">Abstract</x> The toxicity of potassium ferrocyanide (PFC) and protective effects of 2, 4‐dinitrophenol (DNP) under PFC treatment were tested on the Drosophila melanogaster model system. Fly larvae were raised on food supplemented with PFC at concentrations of 1.0 mM and mixtures with DNP in concentrations of 0.50 and 1.25 mM, either alone or in combination with 1.0 mM PFC. Food supplementation with PFC decreased larvae viability or pupation height, whereas when larvae were fed by PFC and DNP combination the decrease was less pronounced. Larval exposure to PFC and mixtures of DNP and PFC lowered activities of aconitase. Larval treatment with PFC resulted in higher carbonyl protein, uric acid, and low molecular mass thiols content and higher activity of thioredoxin reductase in adult flies, while DNP in mixtures with PFC relieved these effects. Furthermore, treatment with PFC/DNP mixtures resulted in higher activities of superoxide dismutase and glutathione‐S‐transferase. It is proposed that PFC toxicity is mainly related to the cyanide and iron ions, released during its decomposition. The potential mechanisms of protective DNP effects against PFC toxicity are discussed.